Estudo das propriedades analgésicas da Achillea millefolium L. (Asteraceae) - Mistieri, M. L A [UNESP]; Thomazo, N. M M [UNESP]; Mataqueiro, M. I. [UNESP]; Queiroz-Neto, A. [UNESP] (My University, 2001)
This study was designed to separately evaluate the analgesic capacity of 15% tea from Achillea millefolium leaves and florid ends. Three different tests were performed. The animals were separated in 3 groups: group I (control) that received water, group II that received florid end tea, and group III that received leaf tea. The first test was the writhing test induced by intraperitoneal injection of acetic acid in male Swiss mice. The second test consisted of the measurement of tail flick reflex latency (TFRL) in male Wistar rats after receiving a painful thermal stimulus. The groups received the teas or water per os, prior to observation. In the third test, the Wistar rats were submitted to an approximately 1 cm long incision in their tails to test the effect of the teas on induced inflammatory pain. The results showed that the effect of the 15% leaf tea on the mice writhing and TFRL test were not statistically significant. The florid ends tea showed a significantly increase in number of writhes in mice and TFRL in rats after administration. With regard to the effect of the teas on inflammatory pain, ingestion of both preparations caused an increase in the force threshold necessary for the avoidance reflex, indicating antihyperalgesic action of both the leaf and florid ends 15% teas of Achillea millefolium.
Study of the analgesic properties of the Achillea millefolium (Asteraceae)
Keywords: Analgesics non-narcotic; Asteraceae; Hyperalgesia; Millefolium; acetic acid; Achillea extract; analgesic agent; unclassified drug; Achillea; analgesic activity; animal experiment; controlled study; inflammation; male; medicinal plant; mouse strain; nonhuman; pain; plant leaf; rat; tail flick test; tea; thermal stimulation; writhing test; Achillea millefolium; Animalia; Rattus norvegicus